2022
DOI: 10.1002/jhet.4443
|View full text |Cite
|
Sign up to set email alerts
|

Diamides conformationally restricted with central amino acid: Design, synthesis, and biological activities

Abstract: Diamide insecticides, represented by chlorantraniliprole (CHL), were widely applied in the control of lepidopteran insects. In efforts to develop bioactive diamides with novel scaffolds, we design and synthesized a series of diamides containing central amino acids to conformationally simulate CHL. Bioassay results indicated that most compounds containing 1‐aminocyclopropane‐1‐carboxylic acid exhibited excellent larvacidal potency against Mythimna separate and Plutella xylostella. After a systematic structure–a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
(37 reference statements)
2
8
0
Order By: Relevance
“…The optimized structures of the complexes were generated by Pymol 1.7.6. 43,45 CoMFA Calculation. The CoMFA calculation was carried out using SYBYL-X 2.0 software.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimized structures of the complexes were generated by Pymol 1.7.6. 43,45 CoMFA Calculation. The CoMFA calculation was carried out using SYBYL-X 2.0 software.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The binding potencies of the superior complex were also evaluated by MM-GBSA free energy analysis encoded in the prime module of Maestro 10.2. The optimized structures of the complexes were generated by Pymol 1.7.6. , …”
Section: Methodsmentioning
confidence: 99%
“…When the reaction was complete, as monitored by TLC, the reaction mixture was concentrated in vacuum, the concentrate was adjusted to pH 7 with sodium bicarbonate, and then extracted with ethyl acetate. The combined organic phase was filtered after drying over anhydrous sodium sulfate and concentrated in vacuum to give intermediate 6 with yields of 95.3% to 96.4% [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…38 Compound 33 showed potential for further optimization as an insecticidal lead with the LC 50 value of 86.8 mg/L, and compound 34 was identified as a potential insecticidal candidate with LC 50 values of 34.920 mg/L against M. separata and 61.992 mg/against P. xylostella. 39 These results demonstrated that adding some electronwithdrawing groups (polyfluoro, cyano, and chlorine) to the benzene ring improves the insecticidal activities of the compounds; however, adding large volumes of the substituted groups might be unsuitable. Despite these findings, no suitable aromatic heterocyclic system has been found to replace the benzene ring.…”
Section: Part Amentioning
confidence: 99%
“…Moreover, Li Zhong’s group designed and synthesized diamide derivatives containing α-amino acids and found that most of the compounds containing an L -phenylglycine skeleton had good insecticidal activities at 500 mg/L . Compound 33 showed potential for further optimization as an insecticidal lead with the LC 50 value of 86.8 mg/L, and compound 34 was identified as a potential insecticidal candidate with LC 50 values of 34.920 mg/L against M. separata and 61.992 mg/against P. xylostella …”
Section: Diamide Derivatives Acting As Ryrs Activatorsmentioning
confidence: 99%